Peculiarities of Inflammation, Oxidative/Nitrosative Stress in L-Ornithine-Induced Acute Pancreatitis - Chooklin S.; Chuklin S.; Shershen G. (Львівський клінічний вісник)
Introduction. The pathogenesis of acute pancreatitis (AP) continues to be a mystery to scientists. However, significant achievements in the field of fundamental research in the last decade have improved the information on pathophysiological processes in the AP. However, despite the progress in understanding early events in AP, addi tional research is needed to quickly and accurately predict the severe course of the disease, as well as more specif ic and purposeful treatment. Indispensable help in this issue is to study the pathogenesis of AP in an experiment in laboratory animals. The aim of the study. Determine the features of inflammatory processes, oxidative and nitrosative stress in Lornithineinduced acute pancreatitis. Materials and methods. Experiment was conducted on 32 white rats of the Wistar line. Rats were divided into two groups: 1 with induced acute necrotizing pancreatitis (16 rats), 2 control (16 intact animals). Acute pancre atitis was caused by intraperitoneal injection of Lornithine (3 g/kg). They conducted a biochemical study, as well as determination of indicators of inflammation, oxidative/nitrosative stress in blood serum and pancreatic tissue. The statistical calculation of the indicators was carried out using nonparametric methods. Results. At experimental AP in rats in the tissue of software significantly (an average of 2.99 times) increased activity of myeloperoxidase (MPO). In this case, the level of Pamylase in serum of blood rats with AP increased by 270.45 %. It was noted that the activity of MPO in the rat’s soft tissue was probably correlated with the concentration of Pamylase in serum. In rats with acute pancreatitis, the activity of inducible (calciumindependent) de novo synthesis of NO increased by 1.9 times compared with the group of intact rats (p = 0.000913). At the same time, activity of calciumdependent NOsynthase in the tissue of software practically did not change. The proportion of physiological constitutive synthesis of NO (oxidic metabolism of Larginine by percentage of cNOS) in the diet of practically healthy rats was, on average, 51.78 ± 4.38 %, whereas in rats with AP, there was a marked decrease of this indicator up to 37.38 ± 5.85 %. According to the results of experimental data, it was determined that the activity of MPO in the software substantially correlated with the activity of iNOS and inversely with the proportion of cNOS, which indicates an increase in the synthesis of pathological NO in the intensification of the inflammatory process in rats at the AP. At the same time, almost the same correlation is determined between the level of Pamylase in blood serum of rats with activity of iNOS (p = 0.000255) and the share of cNOS (p = 0.000015) in the tissue of the software. H2S significantly lowered in Lornithineinduced pancreatitis in rats to 71.71 ± 7.83 mmol/L (in intact rats 91.98 ± 3.22 mmol/L) (p = 0.000004). At the same time, the concentration of H2S significantly correlated inversely with MPO activity in the tissue (p = 0.000005) and iNOS (p = 0.000098), serum Pamylase concentration (p = 0.000001). With the decrease in the level of H2S in serum, the proportion of physiological constitutive synthesis of NO in the software decreased (p = 0.000139). Conclusions. The obtained results of the experiment indicate a significant importance in the pathogenesis of AP oxidative and nitrosative stress, lack of synthesis of physiological gasotransmitters.